(untitled) (Świat Idei i Polityki, 2006)
Transformation of the political system in Poland has created a new friendly environment for the research on the history of social movements, including socialistic program, formulated basing on Marxism. The lack of any ideological pressure and censorship restrictions formed particularly advantageous circumstances for the researchers interested in the history of the socialistic concept. Today one can consider whether the opportunity which appeared by vanishing the ideological corset has been used properly. In the 1990s, the former approach, usually coming down to treating Marxism as religious dogma, was replaced by negation mostly resulting in the elimination of the issue itself. You could observe a tendency to avoid the research on the history of socialistic concept, so necessary after decades of barriers, resulting in passing over in silence or misrepresentations. The foregoing considerations show vital stages of the process of forming program interpretations created basing on Marxism. However, the presented here schematic depiction may also be useful for demonstrating the process of formulating the program constructed as one of a few variants of any doctrine, i.e. a pattern. The choice of Marxism as a program pattern is only a consequence of referring to an instance of the hagiography of the Polish socialistic movement and is strictly related to my interests concerning the history of the Polish socialistic concept. I regard the suggestions presented here as my voice in the discussion lasting since 1990 on the use of research abilities being a result of the political system transformation in Poland